Investigation of the transfer reactions induced by 16O in 27Al and 28Si at Elab = 240 MeV. Issue 1 (1st September 2022) - Seabra, C. C.; Linares, R.; Zagatto, V. A. B.; Cappuzzello, F.; Cavallaro, M.; Carbone, D.; Agodi, C.; Oliveira, J. R. B.
Abstract: In this contribution, we present first experimental results for the deuteron pickup transfer in the 16 O+ 28 Si system at E lab. = 240 MeV. This reaction populates states in the 26 Al target-like nucleus. In the same experimental campaign we have also measured the one-proton transfer 28 Si( 16 O, 17 F) 27 Al and one-neutron transfer 27 Al( 16 O, 17 O) 26 Al at the same beam energy. Comparison between the energy spectrum of these transfer reactions indicate that: i) the one-proton and one-neutron transfers favor the population of the low-lying states; ii) deuteron transfer to the ground state in 26 Al is highly suppressed; iii) the cross-sections for deuteron transfer that populates low-lying states in 26 Al are roughly 3 times less than the one-neutron transfer.